Kecakapan Pihak yang Melakukan Kontrak Digital Melalui Pembelian Online dan Pihak yang Dapat Dimintai Pertanggungjawaban atas Barang yang Sudah Dibeli Menurut Peraturan Perundang-Undangan di Indonesia - Basani, Christin Septina; Saptana, Deni; Suhardini, Eni Dasuki (Journal of Contemporary Law Studies, 2025)
The purpose of this study is to analyze the legal capacity of the parties in a digital online buying and selling contract and to determine the party that can be held accountable for the goods that have been purchased according to the laws and regulations in Indonesia. Technological developments have made developments in all sectors, including in the buying and selling system. Buying and selling now uses more of the internet or what is called online buying and selling. Online buying and selling falls into the category of digital transactions or contracts. The problem that can occur in a digital contract is the capacity of the parties in this case the subjects who make the agreement. It should be noted that digital contracts are the same as conventional contracts which must be subject to Article 1320 of the Civil Code concerning the requirements for the validity of an agreement. The agreement can be canceled if there is a party that does not meet the subjective requirements of Article 1320 of the Civil Code. The subjects in online buying and selling can be done by children who use their parents' or adults' cellphones. So when the party who makes the agreement does not meet the subjective requirements and should be canceled but is not done, the agreement is considered to remain valid. For online buying and selling that has been done by children, the parents or guardians of the child must be responsible. This research is of a normative legal nature by looking at the requirements for the validity of an Agreement from Article 1320 of the Civil Code.